2022
DOI: 10.1016/j.amsu.2021.103191
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil lymphocyte ratio as predictor of mortality in pediatric patients with bacterial meningitis: A retrospective cohort study

Abstract: Background Bacterial meningitis causes high mortality rates among children. Even with early diagnosis and prompt treatment, around 15% of patients die especially in the first and second days after diagnosis. The neutrophil lymphocyte ratio has been reported to be a predicting factor of severity and outcome for patients with pneumonia and sepsis. However, only a few studies are available to rate the neutrophil lymphocyte ratio as a predictor of mortality in bacterial meningitis. This study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Neutrophil-lymphocyte ratio has been demonstrated to correlate with disease severity in critically ill patients and predicts mortality in different pathologies, particularly in the coronary artery disease. [22][23][24][25][26][27] There are two factors that may make the use of neutrophil-lymphocyte ratio more attractive: first, it is not affected by exercise or dehydration, and second, because neutrophils and lymphocytes represent two complementary immune mechanisms. 43 Neutrophil levels are considered an unspecific inflammatory response marker, and lymphocyte levels are a marker of immune regulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophil-lymphocyte ratio has been demonstrated to correlate with disease severity in critically ill patients and predicts mortality in different pathologies, particularly in the coronary artery disease. [22][23][24][25][26][27] There are two factors that may make the use of neutrophil-lymphocyte ratio more attractive: first, it is not affected by exercise or dehydration, and second, because neutrophils and lymphocytes represent two complementary immune mechanisms. 43 Neutrophil levels are considered an unspecific inflammatory response marker, and lymphocyte levels are a marker of immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…22 Additionally, multiple studies have shown that neutrophil-lymphocyte ratio is a strong predictor of mortality and poor outcomes in patients with different diseases such as acute coronary syndrome, 23,24 with malignancies, 25,26 and bacterial meningitis. 27 Therefore, the use of neutrophil-lymphocyte ratio has been proposed to be useful in Kawasaki disease and several studies have reported its effectiveness in the prediction of outcomes in these patients. 28,29 The primary objective of this study was to determine if neutrophil-lymphocyte ratio before or after intravenous gamma globulin therapy could predict refractory disease and coronary artery lesions in paediatric patients with Kawasaki disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, NLR has shown promise in children as a tool for predicting mortality in bacterial meningitis and distinguishing between upper respiratory tract infections and pneumonia. 15,16 The immune response in RSV AB is a multifaceted process, characterized by lymphopenia and altered monocyte activity being common features. [17][18][19][20][21][22][23][24][25] While severe cases of RSV infections are characterized by neutrophilia.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have examined the role of blood markers from routine complete blood counts (CBCs), such as monocyte‐to‐lymphocyte ratios (MLRs) and neutrophil‐to‐lymphocyte ratios (NLRs), in prognosticating severe outcomes in various diseases. Notably, NLR has shown promise in children as a tool for predicting mortality in bacterial meningitis and distinguishing between upper respiratory tract infections and pneumonia 15,16 . The immune response in RSV AB is a multifaceted process, characterized by lymphopenia and altered monocyte activity being common features 17–25 .…”
Section: Introductionmentioning
confidence: 99%